Fermented mycelial biomass of Ganoderma lucidum as a potential additive for juvenile red hybrid tilapia (Oreochromis sp.) / Kumeera Subramaniam - Kumeera , Subramaniam (2020)
The presence of antibiotic compounds in aquaculture is gaining higher interest worldwide due to the emergence as dangerous pollutants of the environment and to human health. However, feed additive play an important role in agriculture to reduce the usage of antibiotics and aquaculture productive performance. Therefore, the polysaccharide produced by Ganoderma lucidum is recognised due to its essential biological activities. Growing biomass from mycelium of Ganoderma lucidum (MGL) through submerged liquid fermentation (SLF) has been a fast and straightforward alternative compared to fruiting bodies. The study aims to observe the inclusion of biomass from MGL as a dietary supplement on growth performance, antioxidant activity and fatty acid profile of red hybrid tilapia (Oreochromis sp) (RHTO). The experimental diets were 5g/kg, 10g/kg and 15g/kg of MB from MGL.Growth performance was measured using growth indicator parameters, antioxidant activity was measured for Glutathione S-Transferase (GST) and Catalase (CAT) while fatty acid profile was determine using the gas chromatography method. From the finding, the highest value for final weight and specific growth rate (SGR) was 35.4g and 2.14 in diet 15g/kg respectively. For feed conversion ratio (FCR) and feed intake (FI), the best result showed by 15g/kg diet. For antioxidants, the 10g/kg shows better results as GST (52.05nmol/mg protein) and CAT (169.04 nmol/min/ml) compared to other diets. There is no significant difference in 10g/kg diet compared to other diets. The finding on fatty acid profiling concludes that 10g/kg shows the best fatty acid profile for this study compared to control, 15g/kg and 5g/kg. Therefore, 10g/kg enhanced the survival, growth performance as well as antioxidant value. Since there is no mortality recorded, the study concludes that MB is a potential natural dietary supplement in the fish feed which helps promote growth and boost the antioxidant activity in fish.